MAO−SIU solar physics collaborations - Rutten, R.J. (Кинематика и физика небесных тел, 2005)
The Kyiv–Utrecht collaboration in solar physics has a long history and a bright future. In this report I highlight some of our joint analyses in the past, discuss the general solar physics context as I see it at present, and describe exciting research challenges which fit the Kyiv–Utrecht expertise and interests.